A deficiency of Dec2 triggers periodontal inflammation and pyroptosis. (28th February 2021) - Oka, Shunichi; Li, Xiaoyan; Sato, Fuyuki; Zhang, Fengzhu; Tewari, Nitesh; Kim, Il‐Shin; Zhong, Liangjun; Hamada, Nobushiro; Makishima, Makoto; Liu, Yi; Bhawal, Ujjal K.
Abstract: Background and Objectives: Periodontal pathogens initiate various diseases and induce inflammatory host responses. The activation of inflammasomes triggers caspase‐1 and interleukin (IL)‐1β‐mediated pyroptosis via gasdermin D (GSDMD). Differentiated embryo chondrocyte 2 (Dec2) is a transcription repressor that controls the expression of genes involved in innate immune and inflammatory responses. However, the effects of Dec2 on inflammasome‐induced pyroptosis in periodontal tissues remain elusive. This study aimed to characterize the activation of Dec2 inflammasomes that contribute to P .  gingivalis lipopolysaccharide (LPS)‐induced pyroptosis and its functional and regulatory importance in periodontal inflammation. Materials and Methods: Human gingival fibroblasts (HGFs) and human periodontal ligament fibroblasts (HPDLFs) were stimulated with P .  gingivalis LPS in vitro . An experimental periodontitis mouse model (wild‐type (WT) and Dec2 KO) was established to profile periodontal pyroptosis. Results: The results demonstrate that P .  gingivalis LPS activates caspase‐1, caspase‐11, and NF‐κB in HGFs and in HPDLFs. siRNA knockdown of Dec2 stimulated the induction and further upregulated LPS‐induced pyroptosis in HGFs and HPDLFs, resulting in the release of IL‐1β. Further, a deficiency of Dec2 alleviated periodontal pyroptosis via the transcriptional induction of GSDMD. In addition, P .  gingivalis ‐induced IL‐1β expression and Dec2‐deficient mice subsequently increased the inflammatory effect of P .  gingivalis in HGFs and in HPDLFs, confirming the importance of Dec2 in the activation of inflammasomes and the regulation of pyroptosis. Conclusion: Our results demonstrate that Dec2 alleviates periodontal pyroptosis by regulating the expression of NF‐κB, caspase‐1 and GSDMD, suggesting that Dec2 is a crucial component of inflammasome activation and subsequent pyroptosis.